A Study of Learning Achievement, Critical Thinking Ability, and Practical Skills Using Phenomenon-Based Learning with Simulation of Grade 10 Student - Runmai, Tontrakun; Keeratichamroen, Wasana (Ratchaphruek Journal, 2023)
This research was to study the students’ learning achievement, critical thinking ability, and practical skills using phenomenon-based learning with simulation It aimed to: 1) Compare learning achievement before and after learning and compare learning achievement after learning with the 70 percent criterion; 2) Compare critical thinking ability before and after learning; and 3) Compare practical skills before and after learning. The sample were the 34 students of grade 10 students at Huaithalaeng Pitthayakhom School. The research instruments were lesson plans of phenomenon-base learning with simulation, an achievement test, critical thinking ability test, and performance test. Data were analyzed by percentage, mean, Standard Deviation and t-test The research findings showed that: 1) Learning achievement after learning was significantly higher than before learning at .05 level, after learning, and learning achievement was significantly higher than 70% criterion at the .05 level. 2) The critical thinking ability after learning was significantly higher than before learning at .05 level, and 3) The students’ practical skills after learning was significantly higher before learning at .05 level.